Synthesis and Antihyperglycemic Activity of [2-(Substituted phenyl)-3-[{4-(1-naphthyl)- 1,3-thiazol-2-yl}amino]-4-oxo-1,3-thiazolidin-5-yl] Acetic Acid - Imran, Mohd.; Lamba, H.S.; Alam, Ozair; Khan, S.A. (Asian Journal of Chemistry, 2010)
The title compounds were prepared by brominating 1-acetyl naphthalene in chloroform followed by condensation with substituted benzaldehyde thiosemicarbazones using ethanol to get 4-(1-naphthyl)-2-(substituted benzylidineamino)-1,3- thiazoles. These thiazole derivatives were then cyclized to title compounds by reacting with thiomalic acid in dioxane using ZnCl2. All the synthesized compounds were characterized on the basis of their IR, 1H NMR, mass and elemental analysis. The antihyperglycemic study was divided into two phases. Phase-I involved evaluation of blood glucose lowering ability of thiazolidinones in normal rats by sucrose loaded model (SLM). It was observed that compound with Ar = 4-nitrophenyl displayed highest antihyperglycemic activity in SLM. Phase-II study included the evaluation of blood sugar by alloxan model. It was observed that most of the compounds exhibited more antihyperglycemic activity than standard drug pioglitazone on 7th day of study. It was also observed that blood glucose lowering effects were more pronounced and stronger in alloxan model.